The vanishing wetlands - Duffy, Trent (New York : F. Watts, 1994)
Explains, through text and photographs, the various types of wetlands and their importance, describes the plants and animals that live in them, and explores different approaches to saving wetlands.
The types of wetlands -- The importance of wetlands -- The flora and fauna of wetlands -- The politics of preservation -- The Everglades and other wetlands -- Mitigation -- The future of wetlands.
Includes bibliographical references (p. 153-155) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Man -- Influence on nature -- United States -- Juvenile literature; Wetland conservation -- United States -- Juvenile literature; Wetland ecology -- United States -- Juvenile literature; Wetland fauna -- United States -- Juvenile literature; Wetland plants -- United States -- Juvenile literature; Wetlands -- United States -- Juvenile literature; Conservation of natural resources; Ecology; Wetland ecology; Wetlands; Conservation of natural resources; Ecology; Wetland ecology; Wetlands